PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V MIS. AL-MUHSININ RIMBA MELINTANG - Wahyuni, Sri; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of reading comprehension skills of students, with an average grade 62.86. Among students who numbered 21 people only 8 students who are skilled with classical completeness 38.10%. This research is a classroom action research (CAR) conducted aims to improve students' reading comprehension skills of class V Mis. Al-Muhsinin Rimba Melintang by implementing cooperative learning model CIRC. Data collection instrument in this paper is a sheet activities of teachers and students and learning outcomes. This thesis presents the preliminary data the students were capable of reading comprehension only 8 students (38.10%) with an average value of 62.86 (Low). Deuteronomy daily on the first cycle, students are able to read a paragraph element comprehension increased by 18 students (85.71%)%) with an average value of 73.81 (Medium). Furthermore, the daily test cycles II, increased again by the number of students able to as many as 19 students (90.48%) with an average value of 83.33 (Height). The percentage of teachers in implementing the learning activities in the first cycle of the first meeting 58.30% (Enough) and the second meeting is 62.50% (Good). In the second cycle of the first meeting 79.20% (Good) and the second meeting is 91.70% (Very Good). Then, the percentage of student activity in the first cycle of the first meeting 55.00% (Enough) and the second meeting is 60.00% (Enough). In the second cycle of the first meeting of 75.00% (Good) and the second meeting is 90.00% (Very Good). The results of the study in class V Mis. Al-Muhsinin Rimba Melintang prove that the implementation of cooperative learning model Cooperative Integrated Reading And Composition (CIRC) can improve students' reading comprehension skills of class V Mis. Al-Muhsinin Rimba Melintang. Key Words: Cooperative cooperative mode integrited reading and composition (CIRC), reading comprehension